2018
DOI: 10.1038/s41598-018-26429-x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic response of breast cancer cells to anacardic acid

Abstract: Anacardic acid (AnAc), a potential dietary agent for preventing and treating breast cancer, inhibited the proliferation of estrogen receptor α (ERα) positive MCF-7 and MDA-MB-231 triple negative breast cancer cells. To characterize potential regulators of AnAc action, MCF-7 and MDA-MB-231 cells were treated for 6 h with purified AnAc 24:1n5 congener followed by next generation transcriptomic sequencing (RNA-seq) and network analysis. We reported that AnAc-differentially regulated miRNA transcriptomes in each c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 118 publications
1
25
0
Order By: Relevance
“…**P < 0.01, compared with miR-NC group, si-NC group or normal tissue group in several kinds of cancers. For example, Li et al found that SNHG7 promoted colorectal cancer progression by acting as a ceRNA of miR-34a and thereby increasing GALN7 expression level [10]. SNHG7 could also accelerate prostate cancer proliferation via miR-503/Cyclin D1 pathway [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…**P < 0.01, compared with miR-NC group, si-NC group or normal tissue group in several kinds of cancers. For example, Li et al found that SNHG7 promoted colorectal cancer progression by acting as a ceRNA of miR-34a and thereby increasing GALN7 expression level [10]. SNHG7 could also accelerate prostate cancer proliferation via miR-503/Cyclin D1 pathway [11].…”
Section: Discussionmentioning
confidence: 99%
“…For example, HOT-TIP, MALAT1 and MEG3 are regarded as important regulators of tumor progression [7]. Small nucleolar RNA host gene 7 (SNHG7), a lncRNA located on chromosome 9q34.3 with a length of 2157 bp, is a novel identified oncogenic gene functioning in different types of human cancers, including breast cancer, bladder cancer, colorectal cancer and prostate cancer [8][9][10][11]. However, little is known about the role of SNHG7 in PC.…”
Section: Introductionmentioning
confidence: 99%
“…These studies identified between 0 and 2761 differentially methylated CpGs, with none of the identified differentially methylated sites overlapping between these studies, and suffered major methodological issues, especially pertaining to incomplete control of confounding and suboptimal preprocessing methods [4]. Nevertheless, four of our detected differentially methylated CpGs in the main analysis were also differentially methylated in the same direction of association (all hypomethylated in breast cancer) in previous epigenome-wide studies, namely cg07180460 (ZSWIM6), cg22731164 (GPR176), and cg18726036 (FKBP5) in a study of blood DNA methylation from the Sister Study [37], and cg02168584 (DLX2-AS1) in a study of genetically predicted DNA methylation of patients from the Breast Cancer Association Consortium [38], all of which have been shown to be dysregulated in breast cancer cell lines [39][40][41][42].…”
Section: Discussionmentioning
confidence: 63%
“…Besides, its increased expression seems to be stimulated by cell-free DNA from colorectal cancer cells [54], and by treating cell lines with chemotherapy agents. Increased expression of the INSIG1 gene was described in breast cancer cell lines after treatment with gemcitabine and 5-FU [55], while decreased expression was detected after treating a laryngeal cancer cell line with low doses of paclitaxel [56], and after anacardic acid treatment in breast cancer cell lines [57].…”
Section: Discussionmentioning
confidence: 99%